2019
DOI: 10.1080/09658211.2019.1661493
|View full text |Cite
|
Sign up to set email alerts
|

The impact of error frequency on errorless and errorful learning of object locations using a novel paradigm

Abstract: Errorless learning (EL) is an approach in which errors are eliminated or reduced as much as possible while learning of new information or skills. In contrast, during trial-and-error − or errorful − learning (TEL) errors are not reduced and are often even promoted. There is a complex and conflicting pattern of evidence whether EL or TEL may result in better memory performance. One major confound in the extant literature is that most EL studies have not controlled for the number of errors made during TEL, result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 65 publications
2
10
0
Order By: Relevance
“…In line with these findings, our results indicate that OA employ a different strategy than YA by relying more on rewarding, positive feedback following correct responses irrespective of the error frequency, whereas the performance of YA could predominantly be influenced by the value of the first error [29]. The present study extends the previous results obtained using the Drawer task in cognitively unimpaired OA by showing that the same pattern of results (i.e., a beneficial effect of EL compared to TEL, but no effect of error frequency on memory outcome) can also be observed in YA [16].…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…In line with these findings, our results indicate that OA employ a different strategy than YA by relying more on rewarding, positive feedback following correct responses irrespective of the error frequency, whereas the performance of YA could predominantly be influenced by the value of the first error [29]. The present study extends the previous results obtained using the Drawer task in cognitively unimpaired OA by showing that the same pattern of results (i.e., a beneficial effect of EL compared to TEL, but no effect of error frequency on memory outcome) can also be observed in YA [16].…”
Section: Discussionsupporting
confidence: 86%
“…enabling us to recall where we have stored our wallet, keys, or glasses) [17]. We hypothesized that YA would perform better after EL compared to TEL, but that error frequency would not influence recall performance in this group, thus replicating previous findings in YA [16]. In addition, Kessels et al [10] and Ariel and Moffat [18] demonstrated that OA perform worse than YA on explicit spatial learning and memory tasks, for instance tasks in which participants had to acquire, store and retrieve the locations of everyday objects in one of five virtual rooms (living room, bedroom, study room, bathroom and kitchen), but that implicit spatial learning, metacognition and navigation were largely preserved at older age.…”
Section: Introductionmentioning
confidence: 52%
See 3 more Smart Citations